Numerical modeling of air-jet flows under the action of an input-exhaust system - Logachev, K.I.; Pusanok, A.I.; Logachev, A.K.; Tolmacheva, E.I. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2015)
Based on the discrete vortex features of polygonal shape, a mathematical model and a computer software are developed to study air-jet flows near a circular suction channel screened by an annular inlet. The parameters of an input-exhaust system with the largest velocity of incoming air are numerically determined.